Prevalence of fungal skin infections in Iranian wrestlers - Ahmadinejad, Z.; Razaghi, A.; Nouri, A.; Hashemi, S.-J.; Asghari, R.; Ziaee, V. (Asian Journal of Sports Medicine, 2013)
Purpose: Fungal infections are one of the most common skin infections. Athletes, especially in contact sports such as wrestlers are the group at risk of fungal skin infections (FSI). The aim of this study was to determine prevalence of FSI and some effective factors in wrestlers in Tehran, Iran.